Correlação entre microestruturas e propriedades mecânicas de ligas Al-Mg solidificadas unidirecionalmente - Oliveira, Eduardo Reis de (2017)
Currently, dozens of different compositions of aluminum alloys are investigated by means of several commercial processes of Casting. These alloys, by virtue of their excellent fluidity, good melt strength mechanical strength, low coefficient of thermal expansion and good resistance to wear. In the solidification processes the final mechanical properties of parts are dependent on the resulting microstructure, this in turn depends on the thermal parameters of solidification, and defects which are difficult to be eliminated later. Therefore, the control of the solidification processes of metals and alloys allows to maximize the mechanical properties of a mechanical component directly applied in engineering projects. However, there is a gap in the literature when it comes to the correlation between crude solidification microstructure and mechanical strength of Al-Mg alloys, especially when solubilizing under transient heat extraction coding. The main goal of this work was study the influence of the solidification parameters on the microstructure and on the mechanical properties. In this sense, the effect of the superheating was also evaluated. From the results with alloys of composition: Al-1wt.% Mg; Al-3wt.% Mg and Al-5wt.% Mg, solidified under three distinct superheat conditions, it was observed that the use of varied overheating led to an essentially dendritic microstructural morphology for the entire range of composition and cooling rates analyzed, nor even with the use of higher values of overheating led to a variation of microstructural morphology. Seaweed dendrites were observed for all compositions. The variation of the scale of the microstructure had little influence on the Vickers microhardness, however an increase about 75% was observed on microhardness when comparing Al-1wt.% Mg and Al-5wt.% Mg alloys. Al-5wt.% Mg alloy presented the highest values of tensile strength.